Spectral optimisation and a novel lighting-design space based on circadian stimulus. (December 2018) - Dai, Q; Cai, W; Hao, L; Shi, W; Wang, Z
With the recent advances in photobiology research and light-emitting diode technology, lighting considering circadian effects and the potential health benefits attract much attention. In this study, we demonstrate that the common practice of spectral optimisation of light for high visual efficacy can potentially lead to very inefficient delivery of circadian stimulus, which contributes to the lack of circadian entrainment that is likely to happen in indoor environments with only electric lighting. To optimise spectra of white light-emitting diodes for circadian efficacy, a four-component colour-mixing method with explicit analytical solutions is introduced. Energy-saving up to 29% is achieved at a target circadian stimulus of 0.35, by switching from the traditional maximum-visual-efficacy strategy to a maximum-circadian-efficacy strategy. Moreover, we propose a framework of a novel lighting-design space which allows practitioners to explore the possible combinations of circadian stimulus, visual illuminance and colour temperature. Solutions are provided for scenarios where activation of the circadian system should be avoided while a reasonable visual brightness appearance is maintained.